Preparation method of dissolved oxygen sensor membrane head and dissolved oxygen sensor membrane head
By using a mixing technology of indicator and polystyrene microspheres in the sensor head of the dissolved oxygen sensor to form a stable fluorescent layer, and combining the reflective layer and light shielding layer, the problem of long response time of the sensor head and easy eluting of the fluorescent layer is solved, achieving a more efficient and durable dissolved oxygen sensing effect.
Patent Information
- Application Number
- CN202210428262.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-04-22
AI Technical Summary
The sensor head of the existing dissolved oxygen sensor has a long response time and the fluorescent layer is easily eluted, which affects the service life and measurement accuracy.
Using a preparation method of dissolved oxygen sensing film head, a stable fluorescent layer is formed by mixing the indicator with polystyrene microspheres and curing it on a quartz sheet. At the same time, a reflective layer and a light shielding layer are added to improve fluorescence efficiency and wear resistance.
Achieve shorter response time and higher wear resistance, reducing the risk of elution of the fluorescent layer, and improving the accuracy and service life of the measurement.
Smart Images

Figure CN114755209B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dissolved oxygen sensors, and particularly relates to a preparation method of a dissolved oxygen sensor membrane head and a dissolved oxygen sensor membrane head. Background Art
[0002] A dissolved oxygen sensor is a sensing device used to measure the amount of oxygen dissolved in water. The measurement of dissolved oxygen concentration in water plays an important role in water quality monitoring. In the prior art, when measuring dissolved oxygen, a sensor that detects dissolved oxygen through fluorescence is used. The sensing membrane head of this type of dissolved oxygen sensor mainly includes a waterproof and breathable membrane, a fluorescent layer and a quartz sheet. In existing sensing membrane heads, the fluorescent layer is mostly obtained by coating / silane polymerization, which is easily washed away, affecting the service life or limiting the use of low-polarity indicators. In addition, the sensing membrane head of existing dissolved oxygen sensors has a long response time and poor wear resistance. Summary of the invention
[0003] The present invention provides a preparation method of a dissolved oxygen sensor membrane head and a dissolved oxygen sensor membrane head, aiming to solve the problems of long response time and easy falling off of the fluorescent layer in the sensor membrane head in the prior art.
[0004] The technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides a method for preparing a dissolved oxygen sensor membrane head, comprising the following steps:
[0006] Preparation of fluorescent layer: 18-22 parts by mass of indicator is dissolved in 0.8-1.2 parts by volume of tetrahydrofuran solution to obtain indicator solution, and the indicator solution is added to 18-22 parts by volume of 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 50-70 minutes to obtain a first mixed solution; then 0.08-0.12 parts by volume of 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 28-32 minutes, and then ultrasonicated for 4-6 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 7.5-8.5 hours, and dried at 95-105°C for 28-32 minutes to solidify to obtain a fluorescent layer; 1 part by mass: 1 part by volume = 1 mg: 1 ml;
[0007] Preparation of the reflective layer: adding acrylic resin, styrene, ethyl acetate, xylene and organic silicone in a mass ratio of 28-32:3-5:9-11:1.8-2.2:0.9-1.1 into a test tube, stirring and dissolving at 48-52°C, cooling to room temperature and spraying on the fluorescent layer, and then drying at 48-52°C to obtain the reflective layer;
[0008] Preparation of the shading layer: Dichloromethane, butyl acetate, polyacrylic resin, polystyrene, carbon black, paraformaldehyde, sulfonamide formaldehyde resin, dimethyl silicone oil, titanium dioxide powder, polyvinyl chloride, ethyl cellulose, and stearic acid are mixed in a mass ratio of 20:10:2:1:0.2:0.5:0.5:5:1:0.8:1:1, stirred and dissolved at 50°C, and then sprayed on the reflecting layer, and dried at 50°C to obtain the shading layer.
[0009] A further improved solution: in the preparation step of the fluorescent layer, 20 parts by mass of an indicator are dissolved in 1 part by volume of a tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 20 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 1 hour to obtain a first mixed solution; then 0.1 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 30 minutes, and then ultrasonicated for 5 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 8 hours, and dried at 100°C for 30 minutes to solidify, to obtain a fluorescent layer.
[0010] A further improved solution: in the preparation step of the fluorescent layer, 18 parts by mass of an indicator are dissolved in 1.2 parts by volume of a tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 18 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 70 minutes to obtain a first mixed solution; then 0.08 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 32 minutes, and then ultrasonicated for 4 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 8.5 hours, and dried at 95°C for 32 minutes to solidify to obtain a fluorescent layer.
[0011] A further improved solution: in the preparation step of the fluorescent layer, 22 parts by mass of an indicator are dissolved in 0.8 parts by volume of a tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 22 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 50 minutes to obtain a first mixed solution; then 0.12 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 28 minutes, and then ultrasonicated for 6 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 7.5 hours, and dried at 105°C for 28 minutes to solidify to obtain a fluorescent layer.
[0012] A further improved solution: During the preparation of the reflective layer, acrylic resin, styrene, ethyl acetate, xylene and silicone are added into a test tube in a mass ratio of 30:4:10:2:1, stirred and dissolved at 50°C, cooled to room temperature and sprayed on the fluorescent layer, and then dried at 50°C to obtain the reflective layer.
[0013] A further improved solution: During the preparation of the reflective layer, acrylic resin, styrene, ethyl acetate, xylene and silicone are added into a test tube in a mass ratio of 29:5:9:2.1:0.9, stirred and dissolved at 50°C, cooled to room temperature and sprayed on the fluorescent layer, and then dried at 50°C to obtain the reflective layer.
[0014] A further improved solution: the indicator is octaethylporphyrin platinum.
[0015] Further improved solution: the thickness of the quartz layer is less than 1mm and the area is 200cm 2 .
[0016] A further improved solution: the thickness of the fluorescent layer is 18-22 μm; the thickness of the reflective layer is 18-22 μm; and the thickness of the shading layer is 18-22 μm.
[0017] A further improved solution: the thickness of the fluorescent layer is 20 μm; the thickness of the reflective layer is 20 μm; and the thickness of the light-shielding layer is 20 μm.
[0018] In a second aspect, the present invention provides a dissolved oxygen sensor membrane head, which is prepared by the preparation method of a dissolved oxygen sensor membrane head described in any scheme of Example 1.
[0019] The beneficial effects of the present invention are:
[0020] Because the indicator (octaethylporphyrin platinum) and the polystyrene microspheres have similar polarity, the polystyrene microspheres will adsorb a large amount of the indicator due to dipole-π and π-π interactions during stirring; based on the above adsorption, the fluorescent layer is not easily eluted; in addition, by drying at 100°C for 0.5h to solidify, the surface of the polystyrene microspheres will form a molten state and will adhere to the surface of the quartz plate, and the molten bonding between the polystyrene microspheres is relatively strong; when the surface of the polystyrene microspheres forms a molten state, the indicator penetrates into the polystyrene microspheres to achieve uniform mixing and protect the indicator; the polystyrene microspheres are low-polarity polymers and cannot be dissolved in water, so as to achieve the effect of not being eluted.
[0021] The light-shielding layer made by the inventive formula is black and has an adsorption effect on external light, preventing external light from affecting the fluorescent effect of the fluorescent layer. The reflective layer configured by the inventive formula is pure white and acts as a partition to separate the black light-shielding layer from the transparent fluorescent layer, reducing the absorption of the fluorescence of the fluorescent layer and its excitation light by the light-shielding layer. At the same time, the pure white reflective layer reflects the fluorescence emitted by the fluorescent layer, which can enhance the fluorescent effect and reduce the use of indicators.
[0022] Polyvinyl chloride, polystyrene and titanium dioxide powder are added to the light-shielding layer, and the obtained light-shielding layer contains abundant micropores and mesopores, has a large porosity, has good oxygen permeability, and reduces the response time of the sensor; in addition, the light-shielding layer ratio of the present invention makes the water contact angle of the light-shielding layer 105°, the light-shielding layer is insoluble in water, has amphiphilic properties, the interface between its surface and the water body is not obvious and is not easy to be hung with bubbles, and the measurement accuracy is high. In addition, the addition of polyacrylic acid resin, paraformaldehyde, sulfonamide formaldehyde resin and stearic acid makes the light-shielding layer have high hardness and good wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a comparison chart of the fluorescence lifetime of the fluorescent film head made by the present invention in a nitrogen atmosphere and an air atmosphere.
[0025] Figure 2 This is a relationship diagram between the response degree and time of the fluorescent membrane head made by the present invention when it is moved from oxygen-free water into air-saturated water.
[0026] Figure 3 The figure is a relationship diagram of the response degree of different indicator contents in the fluorescent film head made by the present invention to different oxygen concentrations.
[0027] Figure 4 This is a transmittance spectrum diagram of the fluorescent film head made by the present invention before and after it is brushed 104,000 times with a cleaning brush.
[0028] Figure 5 This is a test chart of the stability of the fluorescent film head produced by the present invention.
[0029] Figure 6 It is a fitting curve diagram of the fluorescence signal of the fluorescent membrane head made by the present invention changing with temperature in water with an oxygen concentration of 10 ppm. DETAILED DESCRIPTION
[0030] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present invention. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.
[0031] A method for preparing a dissolved oxygen sensor membrane head comprises the following steps:
[0032] Preparation of fluorescent layer: 18-22 parts by mass of indicator are dissolved in 0.8-1.2 parts by volume of tetrahydrofuran solution to obtain indicator solution, and the indicator solution is added to 18-22 parts by volume of 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 50-70 minutes to obtain a first mixed solution; then 0.08-0.12 parts by volume of 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 28-32 minutes, and then ultrasonicated for 4-6 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 7.5-8.5 hours, and dried at 95-105°C for 28-32 minutes to solidify to obtain a fluorescent layer; 1 part by mass: 1 part by volume = 1 mg: 1 ml; wherein the indicator is octaethylporphyrin platinum.
[0033] Preparation of the reflective layer: adding acrylic resin, styrene, ethyl acetate, xylene and organic silicone in a mass ratio of 28-32:3-5:9-11:1.8-2.2:0.9-1.1 into a test tube, stirring and dissolving at 48-52°C, cooling to room temperature and spraying on the fluorescent layer, and then drying at 48-52°C to obtain the reflective layer;
[0034] Preparation of the shading layer: dichloromethane, butyl acetate, polyacrylic resin, polystyrene, carbon black, paraformaldehyde, sulfonamide formaldehyde resin, dimethyl silicone oil, titanium dioxide powder, polyvinyl chloride, ethyl cellulose, and stearic acid are added into a round-bottom flask in a mass ratio of 20:10:2:1:0.2:0.5:0.5:5:1:0.8:1:1 and mixed, stirred and dissolved at 50°C, and then sprayed on the reflecting layer, and dried at 50°C to obtain the shading layer.
[0035] In the preparation steps of the fluorescent layer, three more specific schemes are as follows:
[0036] The first method: in the preparation step of the fluorescent layer, 20 parts by mass of the indicator are dissolved in 1 part by volume of tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 20 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 1 hour to obtain a first mixed solution; then 0.1 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 30 minutes, and then ultrasonicated for 5 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 8 hours, and dried at 100°C for 30 minutes to solidify to obtain a fluorescent layer.
[0037] The second method: in the preparation step of the fluorescent layer, 18 parts by mass of the indicator are dissolved in 1.2 parts by volume of tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 18 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 70 minutes to obtain a first mixed solution; then 0.08 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 32 minutes, and then ultrasonicated for 4 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 8.5 hours, and dried at 95°C for 32 minutes to solidify to obtain a fluorescent layer.
[0038] The third method: in the preparation step of the fluorescent layer, 22 parts by mass of the indicator are dissolved in 0.8 parts by volume of tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 22 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 50 minutes to obtain a first mixed solution; then 0.12 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 28 minutes, and then ultrasonicated for 6 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 7.5 hours, and dried at 105°C for 28 minutes to solidify to obtain a fluorescent layer.
[0039] In the process of preparing the reflective layer, two more specific schemes are as follows:
[0040] The first method: During the preparation of the reflective layer, acrylic resin, styrene, ethyl acetate, xylene and silicone are added into a test tube in a mass ratio of 30:4:10:2:1, stirred and dissolved at 50°C, cooled to room temperature and sprayed on the fluorescent layer, and then dried at 50°C to obtain the reflective layer.
[0041] The second method: During the preparation of the reflective layer, acrylic resin, styrene, ethyl acetate, xylene and silicone are added into a test tube in a mass ratio of 29:5:9:2.1:0.9, stirred and dissolved at 50°C, cooled to room temperature and sprayed on the fluorescent layer, and then dried at 50°C to obtain the reflective layer.
[0042] The sensor membrane head prepared by the present invention has a thickness of 1 mm and an area of 200 cm 2 The thickness of the fluorescent layer is 18-22 μm; the thickness of the reflective layer is 18-22 μm; the thickness of the light shielding layer is 18-22 μm. More specifically, the thickness of the fluorescent layer is 20 μm; the thickness of the reflective layer is 20 μm; the thickness of the light shielding layer is 20 μm.
[0043] The following is a further description of the dissolved oxygen sensor membrane head prepared by the method of the present invention in combination with the test data:
[0044] Figure 1 This is a comparison diagram of the fluorescence lifetime of the fluorescent film head of the present invention in a nitrogen atmosphere and an air atmosphere; Figure 1 From the fitting results on the upper side, it can be seen that the fluorescence lifetime of the fluorescent membrane head in nitrogen is 108 microseconds, and the fluorescence lifetime in air is 32 microseconds. Therefore, the fluorescent membrane head can realize fluorescence sensing of oxygen.
[0045] Figure 2 The relationship between the response degree and time when the oxygen-free water is transferred into the air-saturated water is shown in the figure; Figure 2 It can be seen that the time for the fluorescent film head to respond to 98% is only 120s; while the prior art mostly takes more than 250s; the response time of the present invention is significantly shortened compared with the prior art.
[0046] Figure 3 The graph is the relationship between the response degree of fluorescent membrane heads (films) with different indicator contents to different oxygen concentrations; Figure 3 It can be seen that the indicator content does not affect the response curve, which means that the addition of the reflective layer is beneficial to reducing the addition of the indicator and reducing the cost.
[0047] Figure 4 The transmittance spectra of the fluorescent membrane head before (lower curve) and after (upper curve) washing with a cleaning brush for 104,000 times are shown. The fluorescent membrane head is the most vulnerable part of the sensor for testing dissolved oxygen by the fluorescence lifetime method, so the wear resistance of the fluorescent membrane head is very high. After the fluorescent membrane head in the present invention is washed 104,000 times, the transmittance has basically no obvious change, and the transmittance at the wavelength of 487nm where the change is the largest increases by only 3%, and the wear resistance is good.
[0048] Figure 5 This is an actual test chart of the stability of the fluorescent membrane head. In the actual water sample oxygen concentration test, the value of the fluorescent membrane head is basically stable within 1 hour, with a deviation of about 2.6%, which meets the actual application needs.
[0049] Figure 6 This is a fitting curve of the fluorescence signal of the fluorescent membrane head in water with an oxygen concentration of 10ppm as the temperature changes; the fluorescence lifetime method is often affected by temperature when testing oxygen concentration (the fluorescence lifetime is different at different temperatures), so deducting the influence of temperature is of great significance for the detection of dissolved oxygen. As the temperature changes, the fluorescence signals of the two fluorescent membrane heads gradually decrease with the increase of temperature, showing a linear relationship, and the slopes are -28.0 and -29.2 respectively; this shows that different fluorescent membrane heads have good consistency, which is helpful to deduct the influence of temperature in actual tests.
[0050] In summary, compared with the prior art, the fluorescent membrane head of the present invention has the following advantages: short fluorescence response time and high reaction sensitivity; an additional reflective layer is added, which is beneficial to reducing the addition of indicators and reducing costs; and good wear resistance.
[0051] Embodiment 2:
[0052] This embodiment provides a dissolved oxygen sensor membrane head, which is prepared by the preparation method of a dissolved oxygen sensor membrane head described in any scheme of Embodiment 1; and includes a quartz plate, a fluorescent layer, a reflective layer and a light shielding layer.
[0053] The present invention is not limited to the above optional implementations, and anyone can derive other various forms of products under the enlightenment of the present invention. The above specific implementations should not be understood as limiting the scope of protection of the present invention. The scope of protection of the present invention should be based on the definition in the claims, and the description can be used to interpret the claims.
Claims
1. A method for preparing a dissolved oxygen sensor membrane head, characterized in that: The following steps are involved: Preparation of fluorescent layer: dissolving 18-22 parts by mass of indicator in 0.8-1.2 parts by volume of tetrahydrofuran solution to obtain indicator solution, and adding the indicator solution to 18-22 parts by volume of 2wt% emulsion containing polystyrene microspheres under stirring for 50-70 minutes to obtain a first mixed solution; then adding 0.08-0.12 parts by volume of 0.1M calcium chloride aqueous solution to the first mixed solution, stirring for 28-32 minutes, and then ultrasonicating for 4-6 minutes to obtain a second mixed solution; pouring the second mixed solution onto a quartz plate, volatilizing at room temperature for 7.5-8.5 hours, and drying at 95-105°C for 28-32 minutes to solidify, to obtain a fluorescent layer; 1 part by mass: 1 part by volume = 1 mg: 1 ml; Preparation of the reflective layer: adding acrylic resin, styrene, ethyl acetate, xylene and organic silicone in a mass ratio of 28-32:3-5:9-11:1.8-2.2:0.9-1.1 into a test tube, stirring and dissolving at 48-52°C, cooling to room temperature and spraying on the fluorescent layer, and then drying at 48-52°C to obtain the reflective layer; Preparation of the light-shielding layer: dichloromethane, butyl acetate, polyacrylic resin, polystyrene, carbon black, paraformaldehyde, sulfonamide formaldehyde resin, dimethyl silicone oil, titanium dioxide powder, polyvinyl chloride, ethyl cellulose, and stearic acid are mixed in a mass ratio of 20:10:2:1:0.2:0.5:0.5:5:1:0.8:1:1, stirred and dissolved at 50°C, and then sprayed on the reflective layer, and dried at 50°C to obtain the light-shielding layer; In the preparation step of the fluorescent layer, 20 parts by mass of an indicator are dissolved in 1 part by volume of a tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 20 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 1 hour to obtain a first mixed solution; then 0.1 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 30 minutes, and then ultrasonicated for 5 minutes to obtain a second mixed solution; The second mixed solution was poured onto a quartz plate, evaporated at room temperature for 8 hours, and dried at 100°C for 30 minutes to solidify, thereby obtaining a fluorescent layer; In the preparation step of the fluorescent layer, 22 parts by mass of an indicator are dissolved in 0.8 parts by volume of a tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 22 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 50 minutes to obtain a first mixed solution; then 0.12 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 28 minutes, and then ultrasonicated for 6 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 7.5 hours, and dried at 105°C for 28 minutes to solidify to obtain a fluorescent layer; During the preparation of the reflective layer, acrylic resin, styrene, ethyl acetate, xylene and silicone are added into a test tube in a mass ratio of 30:4:10:2:1, stirred and dissolved at 50°C, cooled to room temperature and sprayed on the fluorescent layer, and then dried at 50°C to obtain the reflective layer.
2. The method for preparing a dissolved oxygen sensor membrane head according to claim 1, characterized in that: In the preparation step of the fluorescent layer, 18 parts by mass of an indicator are dissolved in 1.2 parts by volume of a tetrahydrofuran solution to obtain an indicator solution, and the indicator solution is added to 18 parts by volume of a 2wt% emulsion containing polystyrene microspheres under stirring and stirred for 70 minutes to obtain a first mixed solution; then 0.08 parts by volume of a 0.1M calcium chloride aqueous solution is added to the first mixed solution, stirred for 32 minutes, and then ultrasonicated for 4 minutes to obtain a second mixed solution; the second mixed solution is poured onto a quartz plate, volatilized at room temperature for 8.5 hours, and dried at 95°C for 32 minutes to solidify to obtain a fluorescent layer.
3. The method for preparing a dissolved oxygen sensor membrane head according to claim 1, characterized in that: During the preparation of the reflective layer, acrylic resin, styrene, ethyl acetate, xylene and silicone are added into a test tube in a mass ratio of 29:5:9:2.1:0.9, stirred and dissolved at 50°C, cooled to room temperature and sprayed on the fluorescent layer, and then dried at 50°C to obtain the reflective layer.
4. The method for preparing a dissolved oxygen sensor membrane head according to claim 1, characterized in that: The indicator is octaethylporphyrin platinum.
5. The method for preparing a dissolved oxygen sensor membrane head according to claim 1, characterized in that: The thickness of the quartz plate is less than 1 mm and the area is 200 cm 2 .
6. The method for preparing a dissolved oxygen sensor membrane head according to claim 1, characterized in that: The thickness of the fluorescent layer is 18-22 μm; the thickness of the reflective layer is 18-22 μm; and the thickness of the light shielding layer is 18-22 μm.
7. A dissolved oxygen sensor membrane head, characterized in that: The dissolved oxygen sensor membrane head is prepared by the preparation method of any one of claims 1 to 6.
Citation Information
Patent Citations
Fluorescent dissolved oxygen sensor diaphragm and preparation method thereof
CN110749581A
Preparation method of fluorinated modified fluorescent dissolved oxygen sensing film and coating for preparing protective layer
CN111289482A